2014
DOI: 10.1080/02103702.2014.977105
|View full text |Cite|
|
Sign up to set email alerts
|

The peer review process as an opportunity for learning / La evaluación por pares como oportunidad para el aprendizaje

Abstract: The experience of submitting research manuscripts for review in scientific journals commonly brings about excellent learning opportunities for authors, especially when they are at the beginning of their research careers. Infancia y Aprendizaje invited junior researchers to submit empirical studies for the publication of a special issue titled The peer review process as an opportunity for learning. The present article introduces the special issue. After reviewing several prior works in the field, we present the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 16 publications
0
11
0
11
Order By: Relevance
“…The reason, in the words of Sánchez, García, and del Río (2002a), is that '(the) review process of the original manuscripts from the scientific bodies is only legitimate inasmuch as it is transparent and based on shared criteria and activities and dialogue from the community of scientific creators ' (p. 32, own translation). This effort to explicitly state the most common criteria behind editorial decisions has potential benefits for not only the authors (offering Monereo, & Scheuer, 2014), we began with a specific call for papers, in which Infancia y Aprendizaje invited junior researchers to submit empirical studies for publication in this special issue, titled The peer review process as an opportunity for learning (the original call for papers can be found in the 35/4 issue).…”
mentioning
confidence: 99%
“…The reason, in the words of Sánchez, García, and del Río (2002a), is that '(the) review process of the original manuscripts from the scientific bodies is only legitimate inasmuch as it is transparent and based on shared criteria and activities and dialogue from the community of scientific creators ' (p. 32, own translation). This effort to explicitly state the most common criteria behind editorial decisions has potential benefits for not only the authors (offering Monereo, & Scheuer, 2014), we began with a specific call for papers, in which Infancia y Aprendizaje invited junior researchers to submit empirical studies for publication in this special issue, titled The peer review process as an opportunity for learning (the original call for papers can be found in the 35/4 issue).…”
mentioning
confidence: 99%
“…Similar to our prior call (Bautista et al, 2014), we invited junior researchers in the journal's thematic areas to submit empirical studies for publication. According to the journal's standards, it was specified that literature reviews would not be accepted, that manuscripts should not exceed the limit of 6,500 words (including abstract, keywords, references, tables and figures) and that publication languages were Spanish and English.…”
Section: Call For Papersmentioning
confidence: 99%
“…There is widespread agreement that peer review offers numerous advantages. Many consider this system to be necessary to academic quality, arguing that it provides the greatest guarantee of the transparency and rigour in the science being published (Bautista et al, 2014). Peer review gives authors a formal opportunity to incorporate alternative voices or perspectives, detect any errors or flaws in logic, and enhance readability or structure of their manuscript prior to appearing in the public domain, thus infusing 'added value' into a publication (Luey, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adicionalmente, en la actualidad las universidades públicas enfrentan el riesgo de disminución de fondos dedicados a la investigación debido a la pandemia generada por el COVID-19 (Feyen, 2020), lo que sin duda tendrá repercusiones en el número de publicaciones científicas y la promulgación de sus resultados. A pesar de la antedicha centralidad de las publicaciones científicas, los investigadores formados y en formación suelen encontrarse con limitadas intervenciones orientadas a la enseñanza de las prácticas letradas que rodean el escribir para publicar (Antoniou & Moriarty, 2008;Bautista et al, 2014;Gomez-Nashiki et al, 2014). En ciertas universidades (principalmente norteamericanas y europeas) se ha apoyado a los docentes ofreciéndoles talleres, tutorías y grupos de escritura (McGrail et al, 2006).…”
Section: Introductionunclassified